Review on The Effect of Alcohol Usage as A Fuel Additive in Internal Combustion Engine - Sarbani, Daud; Mohd Adnin, Hamidi; R., Mamat (Warse, 2021)
The transportation sector holds a big share of the emission to the atmosphere. The emission of Green House Gas (GHG) leads to the thinning of the ozone layer. This situation leads to global warming. An international summit in Kyoto 1997 decided to stabilize the Green House Gas (GHG) emission. Therefore, many types of research have been conducted to reduce emissions. Improving engine performance is another method to reduce the amount of gasoline usage. One of the methods is to reduce emissions is by using alternative fuels. hydrogen, alcohol, and biofuel are among the examples. Among the alternatives, alcohol is a very popular alternative used in an internal combustion engine. This paper aims at reviewing the effect of alcohol on the performance and emission of the use of alcohol inside the spark-ignition engine. This review has confirmed that alcohol serves as good alternative fuel, especially if it is mixed at a good ratio with gasoline. With a good blend of alcohol-gasoline, emission can be reduced significantly.